POLICY, PROTECTION OF POLICYHOLDER, AND LIFE INSURANCE EDUCATION TO THE SOCIETY - Hana Sri Juni Kartika (Fakultas Hukum Universitas Gadjah Mada, 2013)
Changes towards betterment of policyholder protection is not proportional to the growth of life insurance company. Policyholders encounter difficulties in asserting their rights when their life insurance companyis in financial straits and served with bankruptcy petition. Life insurance company and regulator have tore-regulate in detail every possible provision contained in a life insurance and ensure that each clausehas been incorporated in the policy, to protect policyholder. The society must be educated to the rightsand responsibility of the policyholder and the insurer, including the protection accorded to policyholders when the life insurance company is on the edge of financial distress or bankruptcy. Peningkatan perlindungan bagi pemegang polis belumlah memadai jika dibandingkan dengan pertumbuhan industri perasuransian. Pemegang polis menghadapi kesulitan untuk mendapatkan haknya ketika perusahaan asuransi menghadapi kondisi keuangan yang tidak sehat dan kebangkrutan. Perusahaan asuransi dan pembuat undang-undang harus mengatur kembali secara rinci semua klausul yang diperlukan dan memastikan bahwa klausul tersebut sudah termuat dalam polis asuransi, khususnyahal-hal yang mengatur mengenai perlindungan bagi pemegang polis asuransi jiwa. Masyarakat perlu diedukasi tentang hak dan tanggungjawab dari pemegang polis dan perusahaan asuransi selaku penjamin, termasuk mengenai perlindungan pemegang polis ketika perusahaan asuransi jiwa menghadapi masalah keuangan atau kebangkrutan.